Sweetpotato As A Food Crop - Utomo, Joko Susilo (Buletin Palawija, 2009)
Sweetpotato as a food crop. Sweetpotato is among the world most important, versatile and under exploited crop in many part of the world, with more than 133 million tons in world annual production and being cultivated in more than 100 countries and it ranks ninth from the viewpoint of total production as a world crops. Sweetpotato contains approximately 30% dry matter and about 80â90% is made of carbohydrate and the rest are composed by protein, lipids, minerals, fibre and vitamins. Sweetpotato is also well-known as a source of minerals and vitamin. Regardless of these general nutritional excellences, sweetpotato is underexploited food item. In attempt to enhance the utilization as food, several food items was produced. The development of ready to serve products includes candied, canned, frozen, restructured products, etc.